The Effect Of Audit Tenure, Auditor Switching, Leverage And Hood Reputation On Audit Lag - Nurlarasati, Haliza; Parinduri, Aina Zahra (Universitas Pahlawan Tuanku Tambusai, 2024)
Examining variables including auditor tenure, auditor switching, leverage, and KAP reputation allowed the researchers to answer the question,